One-Pot Generation of C≡X Bonds from Methyl 2-Siloxycyclopropanecarboxylates: Simple Syntheses of Functionalized Nitriles and Alkynes - Reich, Dorian; Müller, Dennis S.; Schefzig, Luise; Zimmer, Reinhold; Reissig, Hans-Ulrich (Synlett, 2014)
Starting from methyl 2-siloxycyclopropanecarboxylates simple and efficient one-pot procedures are described that lead to β-cyanoesters and methoxycarbonyl-substituted terminal alkynes. The prepared functionalized alkynes were subjected to typical transformations such as [3+2] cycloaddition providing triazole derivatives, Sonogashira coupling, Au-catalyzed hydrophosphorylation or a copper-catalyzed coupling of methyl diazoacetate furnishing alkyne 14 and allene derivative 15. The Pauson–Khand reaction of the enyne 4c afforded a diastereomeric mixture of methyl 5-oxohexahydropentalen-2-carboxylate 16 in moderate yield.
Keywords: cyclopropanes; nitriles; alkynes; Bestmann–Ohira reagent; Click reaction; Pauson–Khand reaction; enol phosphates